Endovascular treatment of cerebral aneurysm: early experience in a Malaysian tertiary centre - Muda, Ahmad Sobri; Zaini, Izwan Zanni; Zakaria, Rozman; Md Ralib @ Md Raghib, Ahmad Razali; Thanabalan, Jegan; Abu Bakar, Azizi (Universiti Kebangsaan Malaysia, 2011)
Universiti Kebangsaan Malaysia Medical Center (UKMMC) started neurointerventional service in August 2008. In this study, we aimed to evaluate the immediate and short term outcome of endovascular treatment (EVT) of cerebral aneurysm during early period of the services. A retrospective study for cerebral aneurysm treated by endovascular technique, from the Neurosurgical and Radiology Department from September 2008 till February 2010 was performed. Patient's demographic data, initial clinical presentation and assessment of the aneurysm were performed. The immediate results and short term assessment post EVT were evaluated based on standard criteria. Recurrence and complications during and following EVT procedures, were recorded. Twenty one patients with total of 22 aneurysms were treated. The mean age was 54.52 years with 57 being males and 43 females. The majority (81) had single aneurysm. The most common site was anterior communicating artery (28 ). Mean aneurysm sac size was 6.19 mm and 2.55 mm for aneurysm neck. At follow-up, 3 (27.2) had a small residual neck. Four patients (37.2) had residual aneurysm filling, but three of them were treated with stent aiming to achieve flow diversion effect instead of complete occlusion during initial treatment. There was no rebleed or rupture from the immediate to follow-up. Significant complications up to 30-days was observed in 4 patients (20) whereby 2 patients showed improvement and 2 patients died (10 mortality rate). Endovascular treatment of cerebral aneurysms performed in our centre had early outcome, morbidity and mortality compared to other higher volume centres. Longer term follow up is needed to evaluate the long termoutcome/occlusion rate, morbidity and mortality.